STUDENT SELF-GOVERNMENT OF SENIOR STUDENTS AS A SOCIAL ORDER (Pedagogy of Higher and Secondary Education, 2010)
The article discusses the views of scholars on the concept of "students' self-government, the role, and place of business of the pupils' self in the process of actialization of the individual leader-paired.
Keywords: leader; self-socialization; students' self-government bodies